A sense of social affiliation of homeless people participating in a soccer tournament - Dariusz Jacek Olszewski-Strzyżowski; Raluca Buhaș; Sorin Buhaș (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2021)
Background: One of the ways of including homeless persons (especially young people) into society is to enable them to actively participate in sports activities. Implementation of an event of international importance entitled the Homeless World Cup is an excellent example of such activities. Material and methods: The main source of data for this article is the research conducted with the participants of the "Homeless World Cup" Tournament in Poznań in 2013. The study was conducted with the use of the questionnaire technique (direct - the tool was a questionnaire containing 21 questions). The survey was anonymous. The respondents had an opportunity to answer more than one question. In total, 12 homeless players, representatives of the Polish National Team, were examined. Results: The subject of the research was a sense of belonging to homeless people involved in sports activities. The athletes took part in systematic training and participated in an international soccer tournament. The homeless had to do with relations permeated by the spirit of rivalry, cooperation and, of course, disciplining moralism. Taking into account this socio-sport reality and considering homeless people with a research intention, it was possible to assume that one of the consequences of their participation in organized social life would be the discovery of social identity and the anticipated sense of attachment and belonging. This was also the goal of the research task - an explanation of this relationship. The results of the study did not confirm the assumed assumption. Homeless people are people at a young age who have not experienced social isolation and a sense of loneliness. They combined practicing sport with expectations of changing their social position and, in particular, achieving the status of employees. The results related to the personal consequences of practicing sport indicate that homeless people see a correlation between training activity and the necessity to change health behaviors. Conclusions: Most of the surveyed players confirm the fact that their taking up sports activities (playing football) in a decisive manner, inter alia, it changed their lives so far, their positive attitude towards themselves and others, improved their family contacts. Their social and interpersonal relations have visibly improved, and there have been positive changes in their social attitudes, and that sport can be an important factor facilitating their inclusion and return to social life (sport as a way out of homelessness).